2022
DOI: 10.3390/molecules27092911
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Extraction Techniques for the Determination of Volatile Organic Compounds in Liverwort Samples

Abstract: This article focuses on the comparison of four popular techniques for the extraction of volatile organic compounds (VOCs) from liverworts of the Calypogeia azurea species. Since extraction is the most important step in the sample analysis of ingredients present in botanical preparations, their strengths, and weaknesses are discussed. In order to determine the VOCs present in plants, selecting the appropriate one is a key step of the extraction technique. Extraction should ensure the isolation of all components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…As the results of this study showed (Supplementary file; Tables S1-S3), the major organic compounds in each extract differed. The findings were consistent with earlier research, indicating that the kind and number of VOCs detected by GCMS depend on the varied solvent extraction techniques [34,41], ratios, and volumes of various organic solvents [40], including the methodology utilized in co-extraction [34].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As the results of this study showed (Supplementary file; Tables S1-S3), the major organic compounds in each extract differed. The findings were consistent with earlier research, indicating that the kind and number of VOCs detected by GCMS depend on the varied solvent extraction techniques [34,41], ratios, and volumes of various organic solvents [40], including the methodology utilized in co-extraction [34].…”
Section: Discussionsupporting
confidence: 91%
“…The chemical constituent of Niamhom (S. nivea Craib) has not been identified yet. However, another plant in the same genus, S. crispus (L.) Bremek has been reported to contain 0.44-2.95 mg/g dry weight of phenolic acids (such as caffeic acid, ferulic acid, gallic acid, chlorogenic acid, and trans-cinnamic acid), 0.33-1.95 mg/g dry weight of flavonoids (such as quercetin, rutin, catechin, apigenin, naringenin, and kaempferol) [34] as well as terpenes (β-amyrin, taraxerone and taraxerol) and stigmasterol [35]. Another Strobilanthes plant, S. cusia (Nees) Kuntze, was reported to have several chemicals in its extract, such as alkaloids (indirubin, indigo, indicant, 4(3H)-quinazolinone), glycosides (uridine, pinoresinol-4-O-β-D-apiosyl-(1→2)-β-D-glucopyranoside, isoacteoside), sterols (β-daucosterol, spinasterol-3-O-β-D-glucopyranoside), pentacyclic triterpenoids (lupenone, betulin), flavonoids (5,7,4 -trihydroxy-6-methoxyflavone, 3 ,4 ,5,7-quadrihydroxyflavanonols), organic acids (4-hydroxy-3-methoxybenzoic acid, lauric acid), anthraquinones (chrysophano), and polysaccharide [36].…”
Section: Discussionmentioning
confidence: 99%
“…The Faustrime fresh fruits (1 kg) were harvested in the ripening stage in the Napoli province of Italy (40.7085; 14.5258) in October 2022. All parts of the fresh fruits were manually separated and extracted with n -hexane (solid–liquid ratio 1:20 w / v ) at room temperature for 2 nights for the extraction of volatile organic compounds (VOCs), as reported by Guzowska et al, 2022 [ 15 ]. For the recovery of the non-volatile compounds, PE, PU, AL, and SE were freeze-dried, pulverized, and extracted with chloroform via maceration (solid–liquid ratio 1:20 w / v ) for 3 nights, 3 times for each solvent [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…These techniques differ in design base and output, experimental conditions such as temperature, solvent, time, etc. towards getting better extraction results in quality and quantity beside cost and eco-friendly environmental aspects [9][10][11][12][13][14][15].…”
Section: Figure (1) Clove (Syzygium Aromaticum L)mentioning
confidence: 99%